Comparison of membrane proteins in drug resistant and sensitive nonsmall cell lung carcinoma cells - Chung, Francisco S. Jr.
A drug resistant nonsmall cell lung carcinoma (adenocarcinoma) cell line was developed by chronic exposure of the cells to Vinblastine sulfate. MIT assay that the Vinblastine sulfate-chronically-treated cells also developed drug resistance against cisplatin and Doxorubicin-HCL. The results showed that the nonsmall cell lung carcinoma cells have developed multidrug resistance.SDS-PAGE patterns showed a lack of high molecular weight proteins in the crude membrane homogenate of the sensitive cell line.The affinity profiles of ATPase active membrane proteins in drug sensitive and drug resistant cells were determined using lectin derived from Concanavalin-A, Tricum vulgaris and Ricinus communis. The nature of membrane ATPase active fractions between the drug sensitive and drug resistant cell was not differentiated using Concanavalin-A and Tricum vulgaris lectin affinity chromatography. However, there was a variance in affinity to Ricinus communis lectin, such that membrane ATPas active in the drug sensitive fractions were non-galactose binding while the drug resistant fractions were galactose binding.Immunoblotting using JSB-1 monoclonal antibody for P-glycoprotein of the crude membrane proteins allowed visualization of the protein bands in the drug resistant cells. Similar protein bands were also demonstrated in the membrane ATPase active fractions from the resistant cell lines but not in the sensitive cells. These findings suggest the significant differences in drug sensitive and drug resistant membrane proteins on the perspective of protein profile in SDS-PAGE, ATPase activity and resistant membrane proteins on the perspective of protein profile in SDS-PAGE, ATPase activity and Western blotting.
Thesis (Master of Science in Biochemistry)--University of the Philippines Manila.
Keywords: Drug resistance in cancer cells; Multidrug resistance; Membrane proteins